Lupus Nephritis: A Literature Review - Bestri Fortuna; Awalia; Puspa Wardhani (Current Internal Medicine Research and Practice Surabaya Journal, 2024)
Systemic lupus erythematosus (SLE) has diverse clinical presentations, including lupus nephritis (LN), if LN manifest the mortality & morbidity will be elevated. The majority of SLE cases found in females, especially during puberty and childbearing age. A comprehensive understanding of the epidemiology, classification, diagnosis, and management of LN is essential for medical practitioners. Initially, the diagnostic process requires clinical examinations to find clinical manifestations. This process then followed by laboratory assessments to diagnose SLE and identify any indication related to kidney damage, commonly proteinuria. Other findings such as haematuria and leukocyturia may also present. Antinuclear antibodies (ANA) test and anti-dsDNA serves as primary diagnostic tool. In addition, kidney biopsy is the gold standard for LN due to its ability to confirm and measure the stadium for treatment guide. The therapy is specifically based on clinical and biopsy findings, categorized by World Health Organization (WHO) into five classes, namely normal, mesangial, focal and segmental proliferative, diffuse proliferative, and membranous. Accurate diagnosis in the initial stage and suitable therapy is crucial to significantly improve the prognosis of LN. In this review, we address some clinical manifestations related to LN and standardised diagnostic assessment tools, with an ultimate goal to improve the outcome of patients with lupus through an individual-specific management.